CLIMATE SIMULATION OF THE LATEST PERMIAN: IMPLICATIONS FOR MASS EXTINCTION - Kiehl J.T.; Shields C.A. (My University, 2005)
Life at the Permian-Triassic boundary (ca. 251 Ma) underwent the largest disruption in Earth's history. Paleoclimatic data indicate that Earth was significantly warmer than present and that much of the ocean was anoxic or euxinic for an extended period of time. We present results from the first fully coupled comprehensive climate model using paleo- geography for this time period. The coupled climate system model simulates warm high- latitude surface air temperatures related to elevated carbon dioxide levels and a stagnate global ocean circulation in concert with paleodata indicating low oxygen levels at ocean depth. This is the first climate simulation that captures these observed features of this time period.
Keywords: Permian; Paleozoic::Permian